2004
DOI: 10.1007/s00209-004-0656-x
|View full text |Cite
|
Sign up to set email alerts
|

Coherent orientations in symplectic field theory

Abstract: We study the coherent orientations of the moduli spaces of holomorphic curves in Symplectic Field Theory, generalizing a construction due to Floer and Hofer. In particular we examine their behavior at multiple closed Reeb orbits under change of the asymptotic direction. The orientations are determined by a certain choice of orientation at each closed Reeb orbit, that is similar to the orientation of the unstable tangent spaces of critical points in finite-dimensional Morse theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
246
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(249 citation statements)
references
References 10 publications
1
246
0
2
Order By: Relevance
“…One can associate a sign ǫ(F ) to each element [F ] of this moduli space [6] and we define the linearized contact differential…”
Section: One Can Associate a Sign ǫ(F ) To Each Element [F ] ∈ Mmentioning
confidence: 99%
“…One can associate a sign ǫ(F ) to each element [F ] of this moduli space [6] and we define the linearized contact differential…”
Section: One Can Associate a Sign ǫ(F ) To Each Element [F ] ∈ Mmentioning
confidence: 99%
“…Each of these m cylinders sits in R '.S 1 D/ as the image of the graph over R S 1 of the function that sends .s; t/ section of this bundle, thus a C -valued function on C . This pair obeys the equations (1)(2)(3)(4)(5) F A D i .1 j˛j 2 /.…”
Section: A Relative Gradings and The Mapˆrmentioning
confidence: 99%
“…It also comes with a natural, complete Kahler metric; but this is not the flat Kahler metric unless m D 1. In any event, this metric defines a symplectic form and thus the Hamiltonian dynamical system that is defined using the time dependent Hamiltonian function (1)(2)(3)(4)(5)(6) h D The spectrum of this operator is a discrete subset of R with finite multiplicities and no accumulation points. What is denoted here by C‚ consists of the elements in C‚ of the form fc g .…”
Section: A Relative Gradings and The Mapˆrmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they showed that the fundamental group π 1 (Ξ(T 3 ), ξ n ) based at any tight contact structure ξ n on T 3 contains an infinite cyclic group. They obtain a similar result in the more general case of T 2 -bundles over S 1 .…”
Section: Introductionmentioning
confidence: 99%